A Smoothed Finite Element-Based Elasticity Model for Soft Bodies. (29th March 2017) - Zhang, Juan; Zhou, Mingquan; Huang, Youliang; Ren, Pu; Wu, Zhongke; Wang, Xuesong; Zhao, Shi Feng
Abstract : One of the major challenges in mesh-based deformation simulation in computer graphics is to deal with mesh distortion. In this paper, we present a novel mesh-insensitive and softer method for simulating deformable solid bodies under the assumptions of linear elastic mechanics. A face-based strain smoothing method is adopted to alleviate mesh distortion instead of the traditional spatial adaptive smoothing method. Then, we propose a way to combine the strain smoothing method and the corotational method. With this approach, the amplitude and frequency of transient displacements are slightly affected by the distorted mesh. Realistic simulation results are generated under large rotation using a linear elasticity model without adding significant complexity or computational cost to the standard corotational FEM. Meanwhile, softening effect is a by-product of our method.